Light‐induced agglomeration of single‐atom platinum in photocatalysis - Denisov, Nikita; Qin, Shanshan; Will, Johannes; Vasiljevic, Bojana Nedić; Skorodumova, Natalia V.; Pašti, Igor A.; Sarma, Bidyut Bikash; Osuagwu, Benedict; Yokosawa, Tadahiro; Voß, Johannes; Wirth, Janis; Spiecker, Erdmann; et al. (Advanced Materials, 2022)
With recent advances in the field of single-atoms (SAs) used in photocatalysis, an unprecedented performance of atomically dispersed co-catalysts has been achieved. However, the stability and agglomeration of SA co-catalysts on the semiconductor surface may represent a critical issue in potential applications. Here we describe the photoinduced destabilization of Pt SAs on the benchmark photocatalyst, TiO2. In aqueous solutions within illumination timescales ranging from few minutes to several hours, light-induced agglomeration of Pt SAs to ensembles (dimers, multimers) and finally nanoparticles takes place. The kinetics critically depends on the presence of sacrificial hole scavengers and the used light intensity. DFT calculations attribute the light induced destabilization of the SA Pt species to binding of surface-coordinated Pt with solution-hydrogen (adsorbed H atoms), which consequently weakens the Pt SA bonding to the TiO2 surface. Despite the gradual aggregation of Pt SAs into surface clusters and their overall reduction to metallic state, which involves >90% of Pt SAs, the overall photocatalytic H2 evolution remains virtually unaffected.<br

Tailorable Nanoparticles for Magnetic Water Cleaning of Polychlorinated Biphenyls - Müller, Lukas; Zehetmeier, Anna; Höfling, Anna; Gaß, Henrik; Voß, Johannes; Krappmann, Daniel; Rockmann, Linda; Harrer, Elias; Zahn, Dirk; Hirsch, Andreas; Halik, Marcus (Small Methods, 2025)
Anthropogenic persistent organic pollutants pose a pressing threat to the environment and human health. They can be found in water bodies all around the world at low but hazardous concentrations. Typical representatives of this contaminant class are polychlorinated biphenyls (PCBs). Here, nanoparticulate core-shell water cleaning agents are presented, which are able to remove PCBs of various chlorination degrees from water. The core consists of superparamagnetic iron oxide nanoparticles (SPIONs) providing a large surface area that can be tuned via self-assembled monolayers (SAMs) composed of phosphonic acid derivates. This shell binds the pollutants non-covalently enabling facile magnetic water remediation. By employing positively charged or hydrophobic SAMs different PCBs can be preferentially removed. Furthermore, these orthogonal functionalities can be integrated into one SPION system. By combining charged and hydrophobic phosphonic acid derivates in so-called binary SAMs the removal preference can be convoluted, which works just as well in real river water. The cost-efficient availability of the base materials for these tailorable nanoparticles is complemented with recyclability laying the foundation for a sustainable water cleaning proces
Keywords: persistent organic pollutants; polychlorinated biphenyls; self-assembled monolayers; superparamagnetic iron oxide nanoparticles; tailorable adsorption; water remediation

Tailoring the Wetting Behavior of Self-Assembled Monolayers by Surface Charge - Vivod, Dustin; Voß, Johannes; Halik, Marcus; Zahn, Dirk (Journal of Physical Chemistry C, 2024)
The wetting of (mixed) self-assembled monolayers (SAMs) is characterized as a function of surface charge. Using a combination of molecular dynamics simulations and contact angle measurements, we unravel the arrangement of dipoles and hydrogen bonds at the interface. Our basis simulation model features alkyl functionalization of an aluminum oxide surface via n-alkyl-phosphonic acid [C18H37-PO(OH)2] molecules, which represents a commonly used hydrophobic SAM surface readily accessible to contact angle measurements. We then probed the effect of charging the alkyl-terminated SAMs to unravel the interplay of local hydrophobicity and the overall dipole arrangement within the droplets. Strikingly, we find that moderate positive charging retains the hydrophobic character and potentially makes the SAMs even more hydrophobic than their uncharged counterpart. We attribute this phenomenon to the hindering of dangling hydrogen atoms at the water-alkyl contact, as a consequence of dipole rearrangements. While our simulation models predict a contact angle increase by 10° as an upper estimate for boosting hydrophobicity, experimental analyses of mixed SAMs using imidazole/alkyl-terminated species showed roughly constant wetting behavior for moderately positive charging.
CRIS-Team Scopus Importer:2024-05-24